2015
DOI: 10.1371/journal.pone.0139487
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey of HIV Testing and Prevalence in Twelve Brazilian Correctional Facilities

Abstract: BackgroundPrior studies have reported higher HIV prevalence among prisoners than the general population in Brazil, but data have been derived from single prisons. The aim of this study was to evaluate HIV testing practices, prevalence and linkage to care among inmates in a network of 12 prisons.MethodsWe administered a questionnaire to a population-based sample of inmates from 12 prisons in Central-West Brazil and collected sera for HIV and syphilis testing from January to December 2013. We evaluated factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
57
1
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 23 publications
5
57
1
23
Order By: Relevance
“…Notably, in countries where this type of study has previously been performed, the rate of HIV infection in prison populations was higher than that found in the general population (8) . This has also been shown to be case in Brazil; studies using the same observational approach as the present study demonstrated that the infection rate in the general population was 0.8% among men (9) , while the rate of HIV infection among the male inmate population ranged from 1.54-5.7% (10) (11) (12) . A similar result was obtained in a study of 333 male inmates at the Penitentiary of Ribeirão Preto, where the prevalence of HIV infection was 5.7% (10) .…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Notably, in countries where this type of study has previously been performed, the rate of HIV infection in prison populations was higher than that found in the general population (8) . This has also been shown to be case in Brazil; studies using the same observational approach as the present study demonstrated that the infection rate in the general population was 0.8% among men (9) , while the rate of HIV infection among the male inmate population ranged from 1.54-5.7% (10) (11) (12) . A similar result was obtained in a study of 333 male inmates at the Penitentiary of Ribeirão Preto, where the prevalence of HIV infection was 5.7% (10) .…”
supporting
confidence: 76%
“…In the State of Santa Catarina, a study involving ~300,000 individuals who donated blood between 2007 and 2013 reported a prevalence of HIV positivity of 1.5% (13) , showing that the prevalence of this virus in the general population is lower than that found in inmate populations. The behavioral habits of the inmates ( Table 2) were not significantly associated with the prevalence of HIV infection (11) (12) . However, limitations inherent to the small sample size meant that it was difficult to analyze the relationship between the prevalence of HIV infection and behavioral habits.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Studies carried out in several countries, including Brazil, showed a high prevalence of HIV and syphilis infections in incarcerated men 3,5,10,11,12,13 and women 2,3,6,14,15,16,17,18,19,20,21 , reinforcing the importance of serological diagnosis in prisons for the implementation of available intervention. However, Brazilian studies have been carried out in isolated prison units.…”
Section: Introductionmentioning
confidence: 96%
“…High prevalence of infectious disease is associated with greater social vulnerability of individuals prior to incarceration 2,3 , greater exposure to risk factors 4 , prison conditions that favor the transmission of these diseases 3,5,6 , and the lack of preventative and control measures such as diagnosis and treatment of infected individuals 3 . A higher prevalence of sexually transmittable diseases can persist throughout the post-incarceration period, as much due to an absence of diagnosis and/or treatment of diseases acquired before or during incarceration, as to the increasing risk of new infection upon re-entry into society 7 .…”
Section: Introductionmentioning
confidence: 99%